Systematic Status of Lygosoma himalayanum tragbulensis Alcock,“1897” 1898 (Sauria: Scincidae) Collected by the Pamir Boundary Commission, 1885 - Das, I.; Dattagupta, B.; Gayen, N. (Folium Publishing Company, 1998)
Lygosoma himalayanum tragbulensis Alcock, «1897» 1898, shown to be a valid taxon of scincid of the genus Asymblepharus Eremtschenko and Szczerbak, 1980, is raised to specific status and redescribed. It is closely related to several other Himalayan species that were formerly placed in the genus Scincella, including A. himalayana, A. ladacensis, and A. sikimmensis. A. tragbulensis (Alcock, «1897» 1898), is known from five examples, including the two syntypes in the collection of the Zoological Survey of India, collected from Tragbul Pass, western Himalayas, in an area claimed by India and Pakistan.